2008
DOI: 10.1007/s11249-008-9300-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Effect of Grinding Corrugated Rail Surface on the Wear Behavior of Pearlitic Rail Steel

Abstract: Rail grinding has become an increasingly permanent way maintenance practice to tackle rail corrugation, as well as extending the rolling contact fatigue life of rails. However, and as far as material loss is concerned, such a grinding is considered as an artificial wear process added to the natural wear. The work presented in this article investigates the quantitative effect of grinding the whole deformed rail surface layer on the overall wear process of the running surface of pearlitic rail steel. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…The topical subject includes cause and mechanism, growth model and prediction, and control and mitigation measurement. The metallurgical, dynamical, and tribological factors connecting with corrugation, including rail steel type, resonance of wheelset and rail, pinned-pinned resonance, train speed, axle load, rail pad stiffness, sleeper span, track irregularities, and rail grinding operations, are all involved (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Because of the different research approaches and specific application contents, despite over a century's worth of studies and research efforts, the fundamental mechanism that causes rail corrugation has not been fully understood and no general agreement on the root cause of corrugation has yet been reached (6,17).…”
mentioning
confidence: 99%
“…The topical subject includes cause and mechanism, growth model and prediction, and control and mitigation measurement. The metallurgical, dynamical, and tribological factors connecting with corrugation, including rail steel type, resonance of wheelset and rail, pinned-pinned resonance, train speed, axle load, rail pad stiffness, sleeper span, track irregularities, and rail grinding operations, are all involved (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Because of the different research approaches and specific application contents, despite over a century's worth of studies and research efforts, the fundamental mechanism that causes rail corrugation has not been fully understood and no general agreement on the root cause of corrugation has yet been reached (6,17).…”
mentioning
confidence: 99%
“…So, the angle range of remaining frameworks of working car B is set as (a 1 , b 1 ) ( Figure 6). The value of a 1 and b 1 is shown in equations (10) and (11)…”
Section: R300 R80 R13mentioning
confidence: 99%
“…Satoh and Iwafuchi 10 studied the effectiveness of rail grinding to predict RCF damage and their experimental results showed that rail grinding was an effective method to reduce RCF. Tyfour 11 explored the effect of grinding-corrugated rail on the wear process of pearlitic rail. Kalousek et al.…”
Section: Introductionmentioning
confidence: 99%
“…5 Rail grinding has become an increasingly used approach to tackle rail corrugation, as well as extending the RCF-free life of rails. 20 The application of rail grinding to different rail lines depends on the actual requirements and local running conditions. The significant benefits obtained by rail grinding have been well-documented and verified by various measurement techniques, such as rail profile scanning Mini-Prof and Corrugation Analysis Trolley.…”
Section: Overview Of the Use Of Rail Grindingmentioning
confidence: 99%